RANCANG BANGUN APLIKASI WEBSITE MANGROVE PADA KAWASAN PAMURBAYA SURABAYA MENGGUNAKAN METODE SCRUM - Pradhana, Ilham Gilang; Hariadi, Bambang; Eko Wulandari, Sri Hariani (Jurnal Sistem Informasi Universitas Dinamika, 2020)
PAMURBAYA area is expected to be a place or means of learning for the community and also as a mangrove conservation activity so that the community can know the importance of conserving mangrove forests for the city of Surabaya. There are several ways of the process of delivering information about the importance of mangroves for the city which is currently run by the manager of PAMURBAYA wiasata areas such as the existence of information space in the PAMURBAYA area, there is also a learning application